New species and new records of Clistopyga (Ichneumonidae: Pimplinae) in Brazil - Higa, Priscilla T.; Victorino, Bárbara I.; Dias, Manoel M.; Dias, Angélica M. Penteado- (Zootaxa, 2024)
Clistopyga magninsula sp. nov. (Pimplinae, Ichneumonidae) from Brazil is described as new. Clistopyga hayesiana Bordera & Sääksjärvi and C. porteri Bordera & Sääksjärvi, previously known only to Paraguay and Argentina respectively, are recorded for the first time in Brazil. We also present a redescription of C. tundisii (Penteado-Dias & Victorino) which was wrongly identified in the genus Zonopimpla.